Correction: Prevalence of Dyslipidaemia and Associated Risk Factors in a Rural Population in South-Western Uganda: A Community Based Survey. - Gershim Asiki; Georgina A V Murphy; Kathy Baisley; Rebecca N Nsubuga; Dermot Maher; Alex Karabarinde; Robert Newton; Janet Seeley; Elizabeth H Young; Anatoli Kamali; Manjinder S Sandhu (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0126166.].